Pengaruh Mobile Banking Dan Automatic Teller Machine Terhadap Kepuasan Nasabah: Studi Kasus PT Bank Central Asia Bogor - Hasanah, Lulu; Listari, Sinta; Efrianti, Desi; Nurjanah, Yayuk (Jurnal Informatika Kesatuan, 2023)
Mobile banking and Automatic Teller Machine (ATM) services are facilities that the banking industry in Indonesia continues to improve to make it easier for customers to transact so that customer satisfaction can be achieved. In the current era of digital banking, all banks in Indonesia continue to compete to provide the best digital services. This study aims to determine the effect of mobile banking and ATM (Automatic Teller Machine) at Bank Central Asia and to find out Bank Central Asia has a significant role in customer satisfaction of Bank Central Asia. The research methodology used is a quantitative approach. The sample used is the customers of Bank Central Asia Bogor City as many as 100 respondents. The results of the research conducted indicate that mobile banking and ATM (Automatic Teller Machine) have an effect on customer satisfaction. The significant level of mobile banking is obtained by the Sig value of 0.001. The Sig value is smaller than 0.001 (0.001 < 0.05) with a percentage of 0.330 or 33%. And compare the value of t count > t table (3,061 > 1,984). The significant level of ATM (Automatic Teller Machine) is 0.015. The Sig value is smaller than 0.015 (0.000 < 0.05) with a percentage of 0.524 or 52.4%. And with t count of 5.712. So that t count > t table (5.712 > 1.984). Mobile banking and ATM (Automatic Teller Machine) services together have a significant effect on customer satisfaction, namely, Ftable at the 5% confidence level (a = 0.05) with a significant value of 0.000 (0.000 <0.05), and the F value table of 3.09 Fcount of 87.765. So that Fcount > Ftable (87.765 > 3.09). Keywords: Mobile Banking, Automatic Teller Machine (ATM), Customer Satisfaction.